ALGORITHMS AND METHODS OF CONTROLLER's OPTIMUM MANAGEMENT BY MODES OF MAIN GAS PIPELINES - Тимків, Дмитро Федорович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The decision of the tasks related to optimization of office hours MG is examined, taking into account the actual being GPA and being LD in a main gas pipeline. The existent charts of controller's management MG are parted on two systems centralized and decentralized. The second chart of controller's management takes certain advantages on firmness of decision and reliability of the realization, related to that for the first type of management necessary very difficult nonlinear dynamic model, and also large volume of controller's information.